Water, Crisis and Climate Change in Uganda: A Policy Brief - Ruettinger, Lukas; Taenzler, Dennis; Musana, Paddy; Bangirana, Narcisio (Initiative for Peacebuilding, 2011)
Although it is endowed with abundant renewable water resources, Uganda faces huge challenges in the water sector. Pressure on and competition around water resources are increasing. Such increasing competition can lead to conflict potential, especially if it results in unequal water access and availability and interacts with other conflict factors, such as marginalisation or past conflicts. At the same time water can also be a source of peace and cooperation if it is managed in an equitable and sustainable way
Keywords: Water; Climate Change; Uganda